INDIVIDUAL WORLD OF IGOR KOSTETSKIY: SYNTAGMATIC ASPECT - Bahriy, M. Ya. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article reveals the peculiarities of individual style in the work of Igor Kostecki in syntagmatic aspect. This makes it possible to isolate specific stylistic features, including the influence of Christian trends, which can be traced in his works of art of the author. Special attention is paid to the study of works of art the artist through the prism of religion.